PENGARUH LOCUS OF CONTROL TERHADAP RESILIENSI NARAPIDANA NON RESIDIVIS DI LAPAS KELAS IIA JAMBI - Walhidayah, Taufiq; Rahayu, Mulyani (Universitas Nusa Cendana, 2024)
Locus of control refers to individuals' beliefs regarding how much they have control over the events in their lives. Meanwhile, resilience refers to an individual's ability to recover and bounce back after experiencing challenges or trauma. This study involved new non-recidivist inmates who had just served a maximum of 1 (one) year in the Jambi Class IIA Correctional Institution. The purpose of this study was to determine and examine the effect of locus of control on the resilience of new non-recidivist inmates at the Jambi Correctional Institution. The population studied was 211 and obtained a sample with the Slovin formula of 102 new non-recidivist prisoners. The method used in this research is quantitative. The result of this study through the regression shows that there is an effect of locus of control on the resilience of new non-recidivist prisoners at the Jambi Penitentiary. Keywords: Locus of Control; Resilience; Correctional Institution